Market Valuation and Employee Stock Options - Zhang, Ge (Management Science, 2006)
This paper investigates a market-valuation-based hypothesis for employee stock options (ESOs). Given that stock prices do not track fundamental values perfectly, I show that ESOs can be used to sell overvalued stocks and to increase long-term shareholder value. The key cross-sectional prediction of the valuation rationale is that the conditional probability of granting options to employees and the amount of options granted to them are positively correlated with market valuation and volatility. Moreover, for extremely overvalued firms, the correlation between option grant and market valuation is weaker. Firms that use ESOs can save their regular employee compensation costs. I find strong empirical evidence supporting these predictions.